2012
DOI: 10.1016/j.jad.2012.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Do burnout and work engagement predict depressive symptoms and life satisfaction? A three-wave seven-year prospective study

Abstract: Work-related well-being predicts general wellbeing in the long-term. For example, burnout predicts depressive symptoms and not vice versa. In addition, burnout and work engagement are not direct opposites. Instead, both have unique, incremental impacts on life satisfaction and depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
550
6
48

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 685 publications
(658 citation statements)
references
References 57 publications
54
550
6
48
Order By: Relevance
“…This result which has been yielded is similar to the results of the research which has found that work engagement by different professional employees is related to life satisfaction (De Cuyper, Notelaers and De Witte, 2009;Hakanen and Schaufeli, 2012;Nilsson et al, 2007;Wessels, 2009;Williamson, 2011). In addition, it is seen that the meaningful contribution to www.ccsenet.org/ies…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This result which has been yielded is similar to the results of the research which has found that work engagement by different professional employees is related to life satisfaction (De Cuyper, Notelaers and De Witte, 2009;Hakanen and Schaufeli, 2012;Nilsson et al, 2007;Wessels, 2009;Williamson, 2011). In addition, it is seen that the meaningful contribution to www.ccsenet.org/ies…”
Section: Discussionsupporting
confidence: 88%
“…While according to one view, the notion of work engagement is conceptualized as an exact opposing notion of burnout (Maslach, Schaufeli and Leiter, 2001;Schaufeli and Bakker, 2004), it is taken up by another viewpoint as a mental state which develops independently from burnout and which is a positive and satisfying state related to work such as vigor, dedication and absorption (Schaufeli and Bakker, 2001;Schaufeli et al, 2002b). A great many research studies reporting that work engagement has positive results for the individual, family and the organization, are related to life satisfaction and predicts the latter in a positively meaningful way are attention drawing (De Cuyper, Notelaers and De Witte, 2009;Hakanen and Schaufeli, 2012;Nilsson, Bernspang, Fisher, Gustafson and Lofgren, 2007;Wessels, 2009;Williamson, 2011). However, it is seen that all these studies which have been conducted were made on workers from different professional groupings and that no study has been conducted on students.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that burnout predicts depressive symptoms and not the opposite, since the latter may arise as a result of the syndrome (28)(29) . This is a very controversial question for inexperienced researchers and has been discussed for many years (5) .…”
Section: Discussionmentioning
confidence: 99%
“…Engaged people experience positive emotions and process information better (Hakanen and Schaufeli 2012). And, they are healthy and have low rates of absenteeism ).…”
Section: Consequences Of Work Engagementmentioning
confidence: 99%